Mitigating construction waste in Nigeria: The role of Building Information Modeling (BIM) at design and pre-contract stages - Omer, Mazen M.; Eze, Emmanuel; Yuan, Hongping; Ameyaw, Ernest; Sofolahan, Onyinye (Elsevier B.V., 2025)
Building Information Modeling (BIM) is revolutionizing the construction industry by providing a digital representation that supports the entire lifecycle of projects. Also, BIM can support the project’s sustainability within the design and pre-contract stages to mitigate construction waste (CW). Therefore, this study investigates Building Information Modelling’s (BIM) effectiveness in mitigating CW in Nigeria’s construction sector, particularly during design and pre-contract stages. It seeks to identify key contributing factors to CW and explore BIM’s potential in addressing these issues. Utilizing a comprehensive literature review, the research identified 37 potential CW causes, incorporating them into a survey for construction professionals. As a result, 133 valid responses were collected and analyzed by using different statistical techniques, including normalized mean technique, quartile analysis, overlapping analysis, contextual disparities analysis, and Spearman’s correlation analysis. The analysis pinpointed 16 critical causes of CW. Significantly, “design complexity”, “errors in contract documents”, “frequent design changes”, and “slow drawing revision and distribution” were identified as paramount. The comparison with previous studies underscores how addressing the critical causes of CW using BIM can contribute to sustainable construction practices. In all, the findings provide valuable insights for mitigating CW in Nigeria and similar contexts in developing economies. Similarly, it can also guide international efforts to reduce CW in construction sectors globally, encouraging countries to address similar critical causes of CW using BIM sustainably. The study advocates for BIM’s early adoption in construction projects to proactively tackle design-related waste.